Dose assessment for the fetus considering scattered and secondary radiation from photon and proton therapy when treating a brain tumor of the mother. (30th December 2015) - Geng, Changran; Moteabbed, Maryam; Seco, Joao; Gao, Yiming; George Xu, X; Ramos-Méndez, José; Faddegon, Bruce; Paganetti, Harald
Abstract: The goal of this work was to determine the scattered photon dose and secondary neutron dose and resulting risk for the sensitive fetus from photon and proton radiotherapy when treating a brain tumor during pregnancy. Anthropomorphic pregnancy phantoms with three stages (3-, 6-, 9-month) based on ICRP reference parameters were implemented in Monte Carlo platform TOPAS, to evaluate the scattered dose and secondary neutron dose and dose equivalent. To evaluate the dose equivalent, dose averaged quality factors were considered for neutrons. This study compared three treatment modalities: passive scattering and pencil beam scanning proton therapy (PPT and PBS) and 6-MV 3D conformal photon therapy. The results show that, for 3D conformal photon therapy, the scattered photon dose equivalent to the fetal body increases from 0.011 to 0.030 mSv per treatment Gy with increasing stage of gestation. For PBS, the neutron dose equivalent to the fetal body was significantly lower, i.e. increasing from 1.5 × 10 −3 to 2.5 × 10 −3 mSv per treatment Gy with increasing stage of gestation. For PPT, the neutron dose equivalent of the fetus decreases from 0.17 to 0.13 mSv per treatment Gy with the growing fetus. The ratios of dose equivalents to the fetus for a 52.2 Gy(RBE) course of radiation therapy to a typical CT scan of the mother's head ranged from 3.4–4.4 for PBS, 30–41 for 3D conformal photon therapy and 180–500 for PPT, respectively. The attained dose to a fetus from the three modalities is far lower than the thresholds of malformation, severe mental retardation and lethal death. The childhood cancer excessive absolute risk was estimated using a linear no-threshold dose-response relationship. The risk would be 1.0 (95% CI: 0.6, 1.6) and 0.1 (95% CI: −0.01, 0.52) in 10 5 for the 9-month fetus for PBS with a prescribed dose of 52.2 Gy(RBE). The increased risks for PPT and photon therapy are about two and one orders of magnitude larger than that for PBS, respectively. We can conclude that a pregnant woman with a brain tumor could be treated with pencil beam scanning with acceptable risks to the fetus.